The Effect of the Flower Chart Strategy on Arabic Grammar Achievement and Information Retention among Fifth Grade Elementary Students (Journal of the College of Basic Education, 2026)
This research aims to identify the impact of the Flower Chart strategy and its relationship to teaching Arabic grammar. Specifically, it seeks to utilize the theoretical foundations of constructivist education and active learning, linking them to the primary stage, which forms the basis for advanced stages in a student's life. Arabic grammar is fundamental to their academic journey. Therefore, this research presents modern strategies that demonstrate their ability to make students more effective in lessons and connect them to real-world applications. The researcher employed an experimental design, including a quasi-controlled design with an experimental group and a control group, and a post-test. The researcher selected six topics from the fifth-grade Arabic grammar textbook to be taught during the experiment, providing recommendations for both researchers and teachers. Forty-nine behavioral objectives were formulated for the topics, aligned with Bloom's three levels of Bloom's Taxonomy (knowledge, comprehension, and application). Appropriate lesson plans were developed and their validity confirmed by a panel of experts, reviewers, and specialists in Arabic language and teaching methodologies. The researcher also prepared an achievement test. Finally, in the subject of Arabic grammar, it consists of (30) items, from the objective items of the (multiple choice) type, and its validity and reliability of (90, 0) were confirmed, and the difficulty, discrimination power and effectiveness of the incorrect alternatives for its items were extracted, and the reliability coefficient of the test was calculated using the test-retest method for the objective items, to ensure the reliability of the correction. Then the researcher applied the test to the students of the two research groups after completing the experiment, which lasted (6) weeks, using the following statistical methods: the t-test, square, chi-square, difficulty coefficient, discrimination coefficient, effectiveness of the incorrect alternatives, test-retest method, and effect size.